STRATEGI PENYALURAN PUPUK BERSUBSIDI DI KECAMATAN WONOTIRTO - Okta Famela; Luhur Aditya Prayudhi; Yuhanin Zamrodah (grafting, 2023)
Fertilizer is a supporting component in the agricultural sector which has the most important role to improve agriculture in Indonesia, this happens because farmers realize that the role of fertilizer greatly influences agricultural yields. Farmers' dependence on fertilizers is getting bigger when the government succeeds in developing agriculture through food self-sufficiency. The need for agricultural production continues to increase along with the increasing rate of population growth, resulting in the need for fertilizer also increasing. This situation forces fertilizer producers to produce optimally in order to meet market demand. This study aims to explain the strategy for distributing subsidized fertilizers in Wonotirto District so that it can help farmers in terms of providing subsidized fertilizer according to the needs of farmers and according to what has been determined in the RDKK (Definitive Plan for Group Needs).